Ten questions concerning the future of ventilation and indoor air quality in European schools - Robert S. McLeod; Ulla Haverinen-Shaughnessy; Pawel Wargocki; Marcel Loomans; Tunga Salthammer; Twan van Hooff; Malcolm J. Cook; Philomena M. Bluyssen; Atze Boerstra; Froukje van Dijken; Michael Swainson; Christina J. Hopfe (Building and Environment, 2026)

Air quality at mass gatherings: assessing ventilation and occupancy in marquees to evaluate airborne infection risk during the COVID-19 pandemic - Ben M. Roberts; Filipa Adzic; Ailsa Hamilton-Smith; Christopher Iddon; Oliver Wild; Malcolm Cook; Steve Gwynne; Aoife Hunt; Liora Malki-Epshtein (Building and Environment, 2026)

Re-evaluating local ventilation effectiveness guidance for single-zone naturally ventilated spaces - Murat Mustafa; Malcolm J. Cook; Robert S. McLeod; Richard de Dear (Building and Environment, 2025)

Experimental evaluation of airflow guiding components for wind-driven single-sided natural ventilation: A comparative study in a test chamber - Nima Najafi Ziarani; Malcolm J. Cook; Paul D. O'Sullivan (Energy and Buildings, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

The role of near-façade flow in wind-dominant single-sided natural ventilation for an isolated three-storey building: An LES study - Nima Najafi Ziarani; Malcolm J. Cook; Farnood Freidooni; Paul D. O'Sullivan (Building and Environment, 2023)

Enhancing non-domestic Passivhaus auditoria ventilation design for improved indoor environmental quality - Murat Mustafa; Malcolm J. Cook; Robert S. McLeod (Building and Environment, 2023)

First record of the copepod Eurytemora herdmani in the Firth of Forth, Scotland - Malcolm Charles Baptie; Rosemary Jayne Foster; Kathryn Barbara Cook (Marine Biodiversity, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)